Scintillators for PGNAA in Mineral Exploration. Issue 1 (1st December 2018) - Petrovic, Snezana; Kepic, Anton; Carson, Michael
Abstract : Current gamma-ray detectors, based upon scintillation, are not likely to perform well in narrow diameter logging-while-drilling (LWD), such as NQ diamond drilling. The normally used halide scintillators of NaI, CsI are considered to not have sufficient resolution to compensate for a lack of stopping power in PGNAA applications. Whereas, BGO, a robust oxide scintillator performs so poorly with respect to resolution, light output, and temperature sensitivity that the higher density and stopping power does not compensate fully for its limitations. We have evaluated several novel halide and oxide scintillators that might improve the viability PGNAA in small diameter LWD application. Specifically, we have looked at CsI, SrI, BGO, CWO, CeBr, GAGG, LaBr, YAP scintillators, and find that CeBr and CWO may be a useful alternative to LaBr in PGNAA applications. Our modelling and analysis indicates that very dense scintillators such as CWO, with moderate resolution capability, or moderate density with high resolution, such as CeBr and LaBr, are the best candidates for measuring line spectra from PGNAA with small, less than 50 mm diameter, detectors. However, none of the newer scintillators are a panacea as the penetrative nature of the PGNAA process means that a high background of scattered gamma rays will obscure many weak elemental peaks even with a "perfect" detector.